Foranotum perforatum gen. et sp. nov.—a new troglobitic darkling beetle (Coleoptera: Tenebrionidae: Kuhitangiinae: Foranotini trib. nov.) from a cave in Southern Zagros, Iran - Nabozhenko, Maxim; Sadeghi, Saber (Zootaxa, 2017)
The troglobitic darkling beetle Foranotum perforatum gen. et sp. nov. from a cave in Southern Zagros Mountains (Iran) is described. This new taxon belongs to the family Tenebrionidae based on the following combination of characters: tarsal formula 5-5-4, antennal insertions concealed from above, antennae 11-segmented, mesocoxal cavities laterally closed by meso- and metaventrite. It is close to Kuhitangia kryzhanovskii Medvedev, 1962 by sharing a similar structure of procoxa (open cavities), labrum (reduced tormal arms) and prothorax (perforating holes on lateral sides of disc). Based on a comprehensive character analysis the subfamily Kuhitangiinae (type genus Kuhitangia Medvedev, 1962) is reestablished. Kuhitangiinae belongs to the pimelioid branch of the family Tenebrionidae based on open mouthparts (mentum small, exposing most of maxillae), mesocoxae externally closed by meso- and metaventrite, metacoxae externally narrowly closed by metaventrite and first abdominal ventrite, tentyrioid structure of abdominal ventrites (absence of membranes between abdominal ventrites 3–5) and absence of defensive glands. The subfamily Kuhitangiinae is divided into following two tribes: Kuhitangiini with a single species Kuhitangia kryzhanovskii Medvedev, 1962 and Foranotini trib. n. with Foranotum perforatum sp. nov. The new tribe differs from Kuhitangiini by the presence of trochanters and epipleura, structure of pronotum, abdominal ventrites and sculpture of meso- and metaventrites.